Optimalisasi Pelayanan Tertib Administrasi Kependudukan Dalam Program Kalimasada Di Kelurahan Tambakrejo Kota Surabaya - Fransiskus Ari Nugraha; Indah Murti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Internship is one component of the learning process in the Bachelor of Public Administration (S1) Study Programme of FISIP UNTAG Surabaya. With the development of MBKM- Merdeka Learning Independent Campus, one of which is MSIB Internships and Certified Independent Study is one of the Independent Campus programmes designed to ensure students get the main, best, and most up-to-date skills and competencies to face the world of the future. The Population and Civil Registration Office of Surabaya City is the place for internship implementation. This programme covers many programmes in population administration and civil registration. Students have the opportunity to choose and seek experience that suits their major on their campus. The researcher will discuss the Kalimasada programme (Kawasan Lingkungan Masyarakat Sadar Administrasi Kependudukan) in this MBKM Dispendukcapil Surabaya internship programme. Kalimasada is one of the Surabaya City Dispendukcapil's programmes to pioneer the creation of an orderly environment/village for civil registration by increasing the number of people who are aware of civil registration. The Population Administration Aware Community Neighbourhood Area (Kalimasada) program is designed to help Surabaya residents get more organised and effective population administration services. Klampid New Generation (KNG) is a platform site where people can access services such as birth certificates, moving in, moving out, and death certificates.